2017
DOI: 10.2147/ott.s138123
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species mediate soft corals-derived sinuleptolide-induced antiproliferation and DNA damage in oral cancer cells

Abstract: We previously reported that the soft coral-derived bioactive substance, sinuleptolide, can inhibit the proliferation of oral cancer cells in association with oxidative stress. The functional role of oxidative stress in the cell-killing effect of sinuleptolide on oral cancer cells was not investigated as yet. To address this question, we introduced the reactive oxygen species (ROS) scavenger (N-acetylcysteine [NAC]) in a pretreatment to evaluate the sinuleptolide-induced changes to cell viability, morphology, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 49 publications
(65 reference statements)
0
32
0
Order By: Relevance
“…MitoSOX Red (Molecular Probes, Invitrogen, Eugene, Oregon) specifically reacted with mitochondrial superoxide (MitoSOX) and generated fluorescence for flow cytometry . Cells were incubated with MitoSOX Red (5 μM) at 37°C for 30 minutes and performed flow cytometry (Accuri C6).…”
Section: Methodsmentioning
confidence: 99%
“…MitoSOX Red (Molecular Probes, Invitrogen, Eugene, Oregon) specifically reacted with mitochondrial superoxide (MitoSOX) and generated fluorescence for flow cytometry . Cells were incubated with MitoSOX Red (5 μM) at 37°C for 30 minutes and performed flow cytometry (Accuri C6).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, oxidative stress‐generating drugs may induce apoptosis . Accordingly, we found that CHW09 induced ROS and apoptosis of Ca9‐22 oral cancer cells in terms of detection of annexin V and cleavage of PARP and cleavage of caspases 3/8/9, suggesting that both intrinsic and extrinsic apoptosis signaling were involved in CHW09‐induced apoptosis.…”
Section: Discussionmentioning
confidence: 83%
“…The signal was explored using WesternBright (ECL HRP: #K‐12045‐D50a; Advansta, Menlo Park, CA). An apoptosis inhibitor Z‐VAD‐FMK (http://selleckchem.com; Houston, TX) (25 μM for 2 hr pretreatment) and a free radical scavenger N ‐acetylcysteine (NAC) (Sigma; St. Louis, MO) (2 mM for 1 hr pretreatment) were used to examine the role of apoptosis and oxidative stress in the CHW09 treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial superoxide interacting dye (MitoSOX Red; Molecular Probes, Invitrogen, Eugene, OR) may generate fluorescence products, which were detectable by flow cytometry . Briefly, cells were treated with MitoSOX Red (5 μM, 37°C) for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%